2019
DOI: 10.1021/acsnano.9b04312
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition Grown Large-Scale Atomically Thin Platinum Diselenide with Semimetal–Semiconductor Transition

Abstract: Among two-dimensional (2D) transition-metal dichalcogenides (TMDCs), platinum diselenide (PtSe 2 ) stands in a distinct place due to its fancy transition from type-II Dirac semimetal to semiconductor with a thickness variation from bulk to monolayer (1 ML) and the related versatile applications especially in mid-infrared detectors. However, achieving atomically thin PtSe 2 is still a challenging issue. Herein, we have designed a facile chemical vapor deposition (CVD) method to achieve the synthesis of atomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
135
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 57 publications
10
135
0
3
Order By: Relevance
“…The authors confirmed the predictions of a semimetal‐to‐semiconductor transition at the monolayer limit, with a band gap of about 1.2 eV. This fascinating effect was supported by Ciarrochi et al., and later‐on Shi et al . determined this transition to already happen at three layers.…”
Section: Properties and Applicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors confirmed the predictions of a semimetal‐to‐semiconductor transition at the monolayer limit, with a band gap of about 1.2 eV. This fascinating effect was supported by Ciarrochi et al., and later‐on Shi et al . determined this transition to already happen at three layers.…”
Section: Properties and Applicationsmentioning
confidence: 98%
“…The performance of the bulk material towards the HER is reasonable, but can be enhanced by increasing the amount of edge sites or by reducing the bulk thickness. Shi et al . indicated atomically thin 1 T ‐PtSe 2 to be a perfect electrocatalyst, with a record high HER efficiency comparable to the traditional Pt catalysts.…”
Section: Properties and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dieser faszinierende Effekt wurde von Ciarrochi et al . verifiziert und später haben Shi et al . herausgefunden, dass dieser Übergang bereits bei nur drei Lagen stattfindet.…”
Section: Eigenschaften Und Anwendungenunclassified
“…Die NMDCs zeigen eine herausragende Leistung als Sensoren, zum Beispiel für Druck oder bestimmte molekulare Spezies . Ihre Chemie, die sehr anisotrope strukturelle Merkmale, geringe Energiebarrieren zwischen den Strukturtypen, kontrollierbare Phasenübergänge und katalytische Eigenschaften beinhaltet, unterscheidet sich von den Übergangsmetalldichalkogeniden (TMDCs) wie MoS 2 oder WSe 2 . Ein Grund dafür ist der Einfluss von Elektronen‐Korrelationseffekten und relativistischen Effekten, wodurch die Untersuchung dieser Materialien seitens der Theorie herausfordernd ist.…”
Section: Introductionunclassified